Green Bonds in India: A Catalyst for Sustainable Development - Durga , Dr.S.; Chandramouli , U.; Podile, Dr Venkateswara Rao (International Journal of Accounting and Economics Studies, 2025)
Green bonds became a key financial tool for financing sustainable development by financing green projects. The impact of green bond issuance on economic growth, investor participation in the Indian market, as well as on sustainability outcomes vis-a-vis regulatory incentives, investor confidence in turn driving green project selection, is presented in this study. The study uses a dataset with 400 samples and uses descriptive statistics, correlation, and regression modeling to evaluate the economic effect of green bonds in various sectors, such as renewable energy, cleansing movement, and sustainable infrastructure. The results show that green bond issuance has a substantial but heterogeneous effect on growth, and that policy incentives should be introduced to make the effect even stronger. Mixed Results in Investors – Investors Are More of a Positive Factor, because when there are Domestic Investors, We See Higher Significance and when we have an International Investor We See Negative Significance, Meaning its Relation with Before there More. These findings underscore the potential of different project categories, as well as the moderate contribution from various categories, potentially informing targeted project interventions in policy effectiveness. The results also indicate a strong correlation between the jobs created by green bonds and India’s sustainable development goals, establishing green bonds as a key driver for long-term development and environmental improvements. This study highlights the importance of implementing standardization in policy, transparency, and diversification of investments in order to maximize the efficiency of India’s green bond market. Overall, this suggests several avenues for future research, e.g., longitudinal studies assessing the impact of different green finance approaches, investor behaviour research and analysis of regulatory innovations to strengthen the green finance framework. With the establishment of strong policies, measures to instill confidence in investors, and efficient project implementation, green bonds can be an effective tool for India to counter-poise its climate commitments with sustainable development and economic growth.